Factors that affect students’ academic performance in UiTM Seremban 3 / Intan Nur Syuhada Abd Rahman, Nor Hidayu Amran and Nurul Syamimi Abdul Khair - Abd Rahman, Intan Nur Syuhada; Amran, Nor Hidayu; Abdul Khair, Nurul Syamimi (2021)
The performance of students as it relates to academic achievement is critical in achieving quality graduates. Many longitudinal experiments are carried out to look at the variables that inﬂuence university students’ results. The main goal of this research is to look at the factors that inﬂuence students’ academic performance at the UiTM Seremban 3 Campus. This study contributes to a greater understanding of the various variables that inﬂuence the student’s academic performance, allowing them to apply to high-level educational institutions. Teaching competencies, ﬁnancial, attendance of students and sleeping habits are among the factors that were examined in this study. Three hundred and ﬁfty students were chosen at random from three faculties: Faculty of Computer and Mathematical Sciences (FSKM), Faculty of Sports Science and Recreation (FSR), and Faculty of Administrative Science Policy Studies (FSPPP). In this analysis, questionnaires were used to gather data and were validated using SPSS software. A multiple linear regression (MLR) analysis was also used to evaluate the relationship between the variables. Findings suggest that ﬁnancial and sleeping habits have a signiﬁcant relationship on students’ academic performance at UiTM Seremban 3. There were a few limitations in this study as well. Failure to acquire data from international students, the use of questionnaires, and the fact that this study was conﬁned to just students from UiTM Seremban 3. Careful techniques and other ways can be used to overcome these restrictions.